SPIRITUALITY AND RESILIENCE OF FORMER DRUG ADDICTS - Nugroho, Dimas Dwi; Huwae, Arthur (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Having the status as a former drug addict who has served his sentence and rehabilitation, it seems that he faces two biggest challenges when returning to society, namely negative stigma and relapse. When facing the challenges of life in society, the ability to renew oneself is needed which is related to spirituality and resilience. The purpose of this study was to determine the relationship between spirituality and resilience in former drug addicts. The method used was quantitative with a correlational design. A total of 55 former drug addicts became participants using incidental sampling techniques. The research measurement used a spirituality scale (? = 0.855) and a resilience scale (? = 0.930). The results showed that there was a significant positive relationship between spirituality and resilience in former drug addicts (r = 0.903 and sig. = 0.000; p <0.01). Spirituality made a strong contribution to the resilience of former drug addicts by 81.5%. (rÂ²). This indicates that spirituality is one of the triggering factors for former drug addicts to be resilient, which includes connectedness with oneself, connectedness with other people or nature, and connectedness with transcendental powers.